1970
DOI: 10.3329/bjas.v37i2.9885
|View full text |Cite
|
Sign up to set email alerts
|

Meat Production Potential Of Different Cross-Bred Ducklings

Abstract: A study was conducted to determine the meat production potential of Pekin (P) x Pekin (P), P x Desi (D) and P x Jinding (J) ducklings up to 8 weeks of age. 54 day old ducklings were randomly allocated to 3 genotypic treatments having 3 replications in each genotype. One duckling from each replication was dissected to determine the meat yield. The initial and final live weight was found highest (P<0.01) in P X P, followed by those of P X D and P X J ducklings respectively. Feed conversion was poor in P X J, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Pekin is mainly raised for meat production and the main goal for crossing ducks with this breed is to improve meatiness (Kokoszynski and Bernacki, 2011;Xie et al, 2014). In a crossbreeding study with Pekin, Deshi and Jinding ducks, the breast meat yield was found significantly higher (P<0.05) in (Pekin × Pekin) than that of (Pekin × Deshi) and (Pekin × Jinding) crossbreds (Ansary et al, 2008) and is consistent with the present study. Similar to the present findings, Kokoszyński et al (2019) found significant effects on preslaughter body weight, carcass weight, breast muscle yield, neck weight, liver weight and gizzard percentage among the three lines of Pekin ducks.…”
Section: Meat Yield Characteristicssupporting
confidence: 90%
“…Pekin is mainly raised for meat production and the main goal for crossing ducks with this breed is to improve meatiness (Kokoszynski and Bernacki, 2011;Xie et al, 2014). In a crossbreeding study with Pekin, Deshi and Jinding ducks, the breast meat yield was found significantly higher (P<0.05) in (Pekin × Pekin) than that of (Pekin × Deshi) and (Pekin × Jinding) crossbreds (Ansary et al, 2008) and is consistent with the present study. Similar to the present findings, Kokoszyński et al (2019) found significant effects on preslaughter body weight, carcass weight, breast muscle yield, neck weight, liver weight and gizzard percentage among the three lines of Pekin ducks.…”
Section: Meat Yield Characteristicssupporting
confidence: 90%